Relationship Between Knowledge and the Incidence of Chronic Energy Deficiency in Pregnant Women - Hasriantirisna (Journal of Public Health and Pharmacy, 2023)
Background: The prevalence of Chronic Energy Deficiency (CED) in pregnant women based on the results of the 2018 Basic Health Research is 17.3%, this result is quite high so that efforts to prevent SEZ must be carried out early. Methods: This research is a quantitative study with 98 samples of shampoo, the data were analyzed by SPSS version 23. Results: The results of the study showed that there was a relationship between knowledge and CED based on the results of p value = 0.043. Discussion: The importance of providing counseling and education to pregnant women to maintain a nutritional balance so that the risk of CED and LBW can be avoided. Conclusion: There is a relationship between knowledge and the risk of CED in pregnant women